Evaluating the Effectiveness of BAZNAS Zakat Distribution on Mustahik Welfare in Ajatappareng Using the CIBEST Model - Yusriadi, Aditya; Damirah, Damirah; Fikri, Fikri; Darmawati, Darmawati; Zubair, Muhammad Kamal (Universitas Muhammadiyah Makassar, 2025)
Zakat distribution in Indonesia has generally been limited to material measurements, which often results in an imbalanced impact on mustahik , especially in the context of productive zakat. To address this gap, the CIBEST (Center for Islamic Business and Economic Studies) model is recognized as an effective tool for measuring both material and spiritual dimensions of welfare. This study focuses on productive zakat recipients ( mustahik ) under the auspices of BAZNAS in the Ajatappareng region, specifically in Parepare City and Sidenreng Rappang Regency. The research adopts a mixed-methods approach, combining quantitative and descriptive qualitative analysis, while using the CIBEST model to evaluate the impact of zakat distribution. Findings reveal that BAZNAS distributes both productive and consumptive zakat—including cash assistance, business equipment, and staple food—alongside training, mentoring, and empowerment programs. Based on the CIBEST quadrant analysis, significant shifts occurred in the material and spiritual poverty classifications of mustahik . Before receiving zakat, households were distributed as follows: Quadrant I (10 households), Quadrant II (22), Quadrant III (0), and Quadrant IV (3). After receiving productive zakat, the distribution changed markedly to: Quadrant I (29 households), Quadrant II (6), Quadrant III (0), and Quadrant IV (0). A paired-sample statistical test showed a significant difference in household income before and after zakat assistance, with a p-value (Sig. 2-tailed) of 0.000 ( 0.05). These findings confirm that productive zakat distribution by BAZNAS has a positive and statistically significant impact on improving the economic welfare of mustahik in the Ajatappareng region.